2018
DOI: 10.1177/1054773818793602
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Cardiovascular Disease Risk Reduction in Korean Americans: A Systematic Review

Abstract: This systematic review was to identify and synthesize literature that described the cultural appropriateness and effectiveness of interventions aimed at cardiovascular risk reduction in Korean Americans. We searched multiple electronic databases for studies published between January 2000 and August 2017 and identified 14 eligible research reports. All reviewed studies targeted first-generation Korean American adults. Most of the reviewed studies incorporated components of surface structure, and leveraged deep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In addition, Filipino American diets are high in salt [32]. Likewise, Korean Americans have diets that are high in salt [33].…”
Section: Assumption: Cultural and Dietary Factors Contributing To Heamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Filipino American diets are high in salt [32]. Likewise, Korean Americans have diets that are high in salt [33].…”
Section: Assumption: Cultural and Dietary Factors Contributing To Heamentioning
confidence: 99%
“…A notable complication of T2DM is heart disease [33]. About three-fourths of deaths in persons with T2DM are a consequence of cardiovascular diseases [51,52].…”
Section: Assumption: Risk And/or Prevalence For T2dm Must Be the Samementioning
confidence: 99%
“…1 A notable difference between Portuguese Americans and other ethnic American populations is evident in their lack of presence in the published health disparities literature. There is much published health disparities research on Cuban, 2 Vietnamese, 3 and Korean Americans, 4 yet Portuguese Americans have received little attention.…”
mentioning
confidence: 99%
“…Highlighting the importance of addressing culture within nursing research, the systematic review of the literature by (Shin et al, 2020) found that interventions were successful in improving cardiovascular health outcomes for Korean Americans. Yet, the role of the participants Korean culture was not consistently addressed in the analysis of the cardiovascular outcomes.…”
mentioning
confidence: 99%
“…Additionally, long-term cardiovascular outcomes were not addressed in the studies reviewed. Shin and colleagues (2020) suggest that by integrating and deploying cultural informed interventions would improve nursing’s ability to decrease cardiovascular health disparities for Korean Americans (Shin et al, 2020).…”
mentioning
confidence: 99%